TECHNOLOGY-ENHANCED LEARNING ENVIRONMENTS: REAL-TIME DATA INTEGRATION IN MARITIME COMPETENCY-BASED TRAINING THROUGH IOT SYSTEMS - Winarno, Winarno; Barasa, Larsen; Simanjuntak, Marihot; Malau, April Gunawan; Suranta, Natanael; Wibowo, Titis Ari (Erudio Journal of Educational Innovation, 2026)
This quasi-experimental research investigated IoT-integrated curriculum effectiveness for maritime competency-based education, addressing workforce preparation needs for technology-intensive operations. Specialized curricular modules incorporating authentic water quality monitoring data from facility IoT systems were implemented with experimental groups (n=45) while control groups (n=42) received traditional instruction. Quantitative assessment revealed statistically significant learning advantages for experimental students across digital literacy (d=1.12), data interpretation (d=1.28), and evidence-based decision-making (d=0.98) competencies. Experimental group competency achievement rates reached 87.3% versus 68.5% for controls (p<.001), representing substantial advancement toward STCW standards. Focus group discussions with students (n=48) revealed enhanced perceived learning authenticity, career relevance, and technology competency development. Instructor interviews (n=8) confirmed observable learning quality improvements while identifying professional development and curricular adaptation requirements. Thematic analysis demonstrated that authentic data engagement catalyzed deeper analytical thinking, sustained engagement, and boundary-crossing learning connecting formal instruction with operational awareness. The research establishes empirical foundation for IoT-integrated pedagogy as effective technology-enhanced learning approach developing critical competencies for contemporary maritime workforce.